Development and validation of multi-residue and multi-class method for antibacterial substances analysis in non-target feed by liquid chromatography – tandem mass spectrometry. Issue 3 (4th March 2018) - Patyra, Ewelina; Nebot, Carolina; Gavilán, Rosa Elvira; Cepeda, Alberto; Kwiatek, Krzysztof
ABSTRACT: A confirmatory HPLC-MS/MS method for the determination of residues of 11 antibacterial substances from different therapeutic class (β-lactams, lincosamides, fluoroquinolones, macrolides, pleuromutilins and sulfonamides) in animal feeds has been developed. The sample preparation is based on extraction with 0.1% formic acid in acetonitrile. Separation of the analytes was performed on biphenyl column with a gradient of 0.1% formic acid in acetonitrile and 0.1% formic acid in Milli-Q water. The developed method was validated following the guidelines included in the European Union Commission Decision 2002/657/EC. Limits of detection ranging from 79.22 to 193.60 µg/kg; instrumental and analytical linearity coefficients were above 0.99 for matrix-match calibration; and relative recoveries ranging from 76.04% to 117.39%. Repeatability of the method was in the range of 2.41–19.76% (CV, %), whereas reproducibility ranged from 6.52 to 28.40% (CV %). The method shown to be efficient and precise for quantification of the 11 antibacterial substances in animal feed. The results demonstrate the feasibility of the method for routine use to monitor these substances in feed. The validated method was successfully applied to eight suspect feed samples collected from the Association of American Feed Control Officials (AFFCO) and feed manufactures from Galicia (Spain) in June and July 2017. Of these 8 non-target feeds, 5 were positive for the presence of tiamulin, tylosin and sulfadiazine.